2013
DOI: 10.1111/nmo.12094
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cholesterol and bile salts in the pathogenesis of gallbladder hypomotility and inflammation: cholecystitis is not caused by cystic duct obstruction

Abstract: A large number of human and animal studies have challenged the hypothesis that cystic duct obstruction by gallstones causes cholecystitis. These studies suggest that lithogenic bile that can deliver high cholesterol concentrations to the gallbladder wall causes hypomotility and creates a permissive environment that allows normal concentrations of hydrophobic bile salts to inflame the mucosa and impair muscle function inhibiting gallbladder emptying. High concentrations of cholesterol increase its diffusion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Gallbladder hypokinesia is defined as gallbladder hypomotility in response to normal physiologic stimuli and results in pathogenic alterations to bile including supersaturation of cholesterol and hydrophobic bile acids [3,4]. Exposure of gallbladder epithelial and smooth muscle cells to concentrated biliary constituents causes hypersecretion of mucus and inflammation via oxidative damage (H 2 O 2 ) and lipid peroxidation; the consequences of which results in the development of gallbladder sludge, mucus plugs, gallstones, cholecystitis, and biliary colic [5][6][7][8][9][10]. Biliary stasis has been linked to many common conditions in humans including obesity, hyperglycemia, hypothyroidism, hypertriglyceridemia, acalculous cholecystitis, pregnancy, and vitamin D deficiency [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Gallbladder hypokinesia is defined as gallbladder hypomotility in response to normal physiologic stimuli and results in pathogenic alterations to bile including supersaturation of cholesterol and hydrophobic bile acids [3,4]. Exposure of gallbladder epithelial and smooth muscle cells to concentrated biliary constituents causes hypersecretion of mucus and inflammation via oxidative damage (H 2 O 2 ) and lipid peroxidation; the consequences of which results in the development of gallbladder sludge, mucus plugs, gallstones, cholecystitis, and biliary colic [5][6][7][8][9][10]. Biliary stasis has been linked to many common conditions in humans including obesity, hyperglycemia, hypothyroidism, hypertriglyceridemia, acalculous cholecystitis, pregnancy, and vitamin D deficiency [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the data demonstrate that the overall concentration of gallbladder cholesterol is significantly decreased in germ-free mice. This decrease in cholesterol concentration may be due to increased Muc1 expression because Muc1 induction has been shown to increase cholesterol absorption from gallbladder bile which in turn has been shown to promote gallbladder inflammation and hypomotility [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, plasma CCK level was significantly decreased in patients with gallstones. [ 14 ] A reduced and delayed postprandial gallbladder contractility and impaired CCK release in the early postprandial phase have been shown to be significantly associated with gallstone disease. [ 15 ] In this study we found decreased plasma CCK level and increased biliary cholesterol and CSI in CGS patients compared with non-CGS patients.…”
Section: Discussionmentioning
confidence: 99%